2014
DOI: 10.1108/jcs-05-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life Scale for Children (QoL-C)

Abstract: Purpose-There is a lack of valid and reliable generic measures of Health Related Quality of Life(HRQoL) for children under eight. This was a preliminary study to assess the psychometric properties of the newly formulated Quality of Life Scale for Children (QoL-C), which uses a pictorial response format.Method-335 primary school children completed the QoL-C on two occasions, two weeks apart. Children aged 4-7 were interviewed one-to-one whilst children aged 8-9 completed the measure as a class activity. Test re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Table D in the Supplementary Information (see the electronic supplementary material) describes the background concepts and development methods for measures, including whether and how children (or parents/primary caregivers in case of infants, toddlers or pre-schoolers) were involved in [37]; two cognitive interviews [6,38]; one feasibility testing [60]; and five made little or no mention of children's involvement [54,[61][62][63][64]. Twenty-three measures reported no involvement of children, relying on clinical and/or research expertise for domain/item elicitation, using statistical techniques for item selection (e.g.…”
Section: Content Validity Of Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Table D in the Supplementary Information (see the electronic supplementary material) describes the background concepts and development methods for measures, including whether and how children (or parents/primary caregivers in case of infants, toddlers or pre-schoolers) were involved in [37]; two cognitive interviews [6,38]; one feasibility testing [60]; and five made little or no mention of children's involvement [54,[61][62][63][64]. Twenty-three measures reported no involvement of children, relying on clinical and/or research expertise for domain/item elicitation, using statistical techniques for item selection (e.g.…”
Section: Content Validity Of Measuresmentioning
confidence: 99%
“…The use of PROMs in childhood populations (aged ≤ 18 years) presents methodological challenges compared to application in adults. One challenge is to account for age-based biopsychosocial developmental differences between children and adults and across children of different ages [5][6][7]. Distinguishing the age or age group of the target childhood population is important for content validity or concept coverage of the childhood PROM, its capacity for child self-report, appropriate design, and the culturally appropriate age for child self-report [2].…”
Section: Introductionmentioning
confidence: 99%
“…Our feasibility work suggested that our very young sample struggled to understand the concepts involved, which, combined with a lack of evidence to support the reliability and validity of the EQ-5D-Y among children under the age of 8 years, led us to drop the measure from the protocol. 76 Instead, a published algorithm was used to map SDQ scores to the Child Health Utility Index 9 Dimensions (CHU-9D), a generic preference-based health-utility measure that combines children's length of life and quality of life into a single summary measure 77 and thus allows comparison of interventions in a decisionmaking context. The CHU-9D was not considered for direct measurement in the study because, at the time of designing and implementing the study, no valuation system was available and the measure was not validated for use with 5-to 6-year olds.…”
Section: Discussionmentioning
confidence: 99%
“…151 Feasibility work that we conducted of a child version of the EQ-5D suggested that our very young sample struggled to understand the concepts involved and that the measure was not valid or reliable. 76 The economic evaluation was also limited by failing to consider spillover effects in teachers' quality of life. TCM has been designed to increase the well-being of teachers as well as of students, and future research should attempt to capture these effects by directly administering a preference-based quality-of-life instrument such as the EQ-5D, which is commonly used in adults.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Moreover, discrepancies between child and informant ratings have commonly been found larger in younger children (about 5 to 7 years) than in older children (e.g., Yi-Frazier et al, 2016). Some researchers have taken these discrepancies as an argument for administering scales to children instead of using parent informant reports (e.g., Jozefiak, 2014; Thompson et al, 2014; Yi-Frazier et al, 2016), “there is a disconnection between parents’ and youths’ perceptions of youth HRQOL” (Yi-Frazier et al, 2016), while others suggest that discrepancies may be an indication of children’s incapability of producing reliable and valid self-report data (Woolley, Bowen, & Bowen, 2004).…”
mentioning
confidence: 99%